Youth experiences of transition from child mental health services to adult mental health services: a qualitative thematic synthesis - Broad, Kathleen L.; Sandhu, Vijay K.; Sunderji, Nadiya; Charach, Alice (BMC psychiatry, 2017)
Background Adolescence and young adulthood is a vulnerable time during which young people experience many development milestones, as well as an increased incidence of mental illness. During this time, youth also transition between Child and Adolescent Mental Health Services (CAMHS) to Adult Mental Health Services (AMHS). This transition puts many youth at risk of disengagement from service use; however, our understanding of this transition from the perspective of youth is limited. This systematic review aims to provide a more comprehensive understanding of youth experiences of transition from CAMHS to AMHS, through a qualitative thematic synthesis of the extant literature in this area. Method Published and unpublished literature was searched using keywords targeting three subject areas: Transition, Age and Mental Health. Studies were included if they qualitatively explored the perceptions and experiences of youth who received mental health services in both CAMHS and AMHS. There were no limitations on diagnosis or age of youth. Studies examining youth with chronic physical health conditions were excluded. Results Eighteen studies, representing 14 datasets and the experiences of 253 unique service-users were included. Youth experiences of moving from CAMHS and AMHS are influenced by concurrent life transitions and their individual preferences regarding autonomy and independence. Youth identified preparation, flexible transition timing, individualized transition plans, and informational continuity as positive factors during transition. Youth also valued joint working and relational continuity between CAMHS and AMHS. Conclusions Youth experience a dramatic culture shift between CAMHS and AMHS, which can be mitigated by individualized and flexible approaches to transition. Youth have valuable perspectives to guide the intelligent design of mental health services and their perspectives should be used to inform tools to evaluate and incorporate youth perspectives into transitional service improvement. Trial registration Clinical Trial or Systematic Review Registry: PROSPERO International Prospective Register of Systematic Reviews CRD42014013799 .